Framing Classroom Discussion of Same‐Sex Marriage. Issue 5 (18th October 2013) - Hand, Michael
Abstract Assuming that the issue of same‐sex marriage should be discussed in schools, how should the discussion be framed? Michael Hand first distinguishes this question from the related but distinct question of whether discussion on this topic should be steered. He then examines three possible frames for discussion of same‐sex marriage: the perfectionist frame, the antiperfectionist frame, and the practical accommodation frame. He defends the perfectionist frame over the two alternatives: the purpose of state involvement in marriage is to promote valuable forms of intimate relationship, so the case for enabling same‐sex couples to marry turns on the ethical claim that same‐sex and opposite‐sex intimate relationships are similarly valuable. Interrogation of this ethical claim must be central to classroom discussion of same‐sex marriage.